2019
DOI: 10.17580/or.2019.06.08
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of energy efficiency in the use of vibration-type process machines in resonant and superresonant operating modes

Abstract: Please replace [at] with @) Committed to improve the Quality of Life For more articles on mechanical maintenance, visit www.practicalmaintenance.netThe information contained in this booklet represents a significant collection of technical information about construction, working and maintenance of electric vibrators and vibrating screens. This information will help to achieve increased reliability at a decreased cost. Assemblage of this information will provide a single point of reference that might otherwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…When calculating the dependence of the amplitude of acceleration on the frequency of rotation of the unbalances, the effect of changing the supply voltage frequency was taken into account. As a result of taking into account the law of frequency regulation, Kloss's formula takes the form [10]:…”
Section: Calculation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When calculating the dependence of the amplitude of acceleration on the frequency of rotation of the unbalances, the effect of changing the supply voltage frequency was taken into account. As a result of taking into account the law of frequency regulation, Kloss's formula takes the form [10]:…”
Section: Calculation Resultsmentioning
confidence: 99%
“…One of the creating energy-efficient vibrating machines principles is based on the use of working body resonant modes of vibration. At the same time, the required masses of unbalances and electric motor power are significantly reduced, which leads to an increase in the efficiency and service life of vibration exciters [3,10,11]. However, maintaining such an operation mode requires the use of automated systems for collecting, processing and analyzing information about the current state of the machine dynamic characteristics with the control actions simultaneous formation [3,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to the fact that in the operating mode, the electric motor is significantly underloaded, as a result of which energy consumption increases and the engine's service life decreases. In works [1,5], using the example of analyzing the power consumption of a technological vibration machine, the calculated values of the required motor power (consumptions associated with vibration impact on the material and friction in bearings) were obtained, which are much less (approximately half) of the installed power. The excess of the installed power (the power required to maintain the required technological mode) in relation to the required one is mainly due to the required power to pass through resonance and raise debalances when starting the machine.…”
Section: Introductionmentioning
confidence: 99%
“…One of the ways to increase the energy efficiency of vibration machines is the use of resonant modes of their working body oscillation, which, however, are usually unstable. In work [5], based on a comparative analysis of energy consumption for the implementation of the beyond-resonant and resonant modes of oscillations of the technological vibration machines' working body with an unbalance vibration exciter, it is shown that the required electrical power of the resonant machine is approximately three times less than that of the beyond-resonant machine. Thus, resonant vibration machines can use less powerful vibration exciters with lighter debalances, which provide a higher stability of their rotation at a significantly lower weight and cost.…”
Section: Introductionmentioning
confidence: 99%